(untitled) - Davidson, P. Michael (London, 2005)
Twelve years have passed since its last edition - making Antimicrobials in Foods, Third Edition the must-have resource for those interested in the latest information on food antimicrobials. During that time, complex issues regarding food preservation and safety have emerged. A dozen years ago, major outbreaks of Escherichia coli O157:H7 and Listeria monocytogenes had not yet occurred, consumer and regulatory demands for improved food safety were just surfacing, the use of naturally occurring antimicrobials was in its infancy, and lysozyme, lactoferrin, ozone, and several other compounds were not approved for use in or on foods in the United States. The editors have addressed these contemporary topics by synthesizing information from internationally recognized authorities in their fields. Five new chapters have been added in this latest release, including the most recent details on lysozyme, naturally occurring antimicrobials from both animal and plant sources, hurdle technology approaches, and mechanisms of action, resistance, and stress adaptation. Existing chapters have been extensively revised to reflect the most relevant research and information available on antimicrobials. Complementing these topics is information on the progress that has been made in determining the effects and mechanisms of action involved in a number of naturally occurring antimicrobials.
Keywords: Food additives,Anti; Infective agents